Fate of Pollution Emitted During the 2015 Indonesian Fire Season. Issue 9 (30th April 2021) - Park, Mijeong; Worden, Helen M.; Kinnison, Douglas E.; Gaubert, Benjamin; Tilmes, Simone; Emmons, Louisa K.; Santee, Michelle L.; Froidevaux, Lucien; Boone, Chris D.
Abstract: The El Niño‐driven fire season in Indonesia in September–October 2015 produced the largest fire emissions on record since NASA's EOS satellites started making observations of tropospheric pollutants from space. In this study, measurements of carbon monoxide (CO) from the Measurement of Pollution in the Troposphere (MOPITT) on Terra and the Microwave Limb Sounder are used to characterize the anomalously high CO emitted during the 2015 Indonesian fire season transported into the tropical upper troposphere and stratosphere. The satellite measurements indicate that CO emitted from wildfires was transported into the upper troposphere with time lags up to ∼2 months and continued to be transported into the stratosphere, which resulted in higher concentrations of CO extending up to ∼20 hPa by the end of 2016. Hydrogen cyanide (HCN) measured by the Atmospheric Chemistry Experiment Fourier Transform Spectrometer (ACE‐FTS) confirms that anomalously high HCN emitted from the same wildfires was also transported into the tropical stratosphere and persisted throughout 2017. Simulations of CO from the Community Atmosphere Model with Chemistry (CAM‐chem) show a significant increase in CO concentrations in the troposphere in October 2015. However, comparisons between CAM‐chem and MOPITT CO suggest that the model underestimates the amount of CO even with doubled emissions of CO in October 2015. Both the satellite measurements and the model simulations show that the pollution emitted from the wildfires over Indonesia was transported to and persisted in the tropical stratosphere much longer than the previous El‐Niño driven fire events due to unprecedented amount of the fire emissions. Key Points: Anomalously high carbon monoxide (CO) emitted during the 2015 Indonesian fire season was transported into the upper troposphere and lower stratosphere Satellite measurements of hydrogen cyanide (HCN) indicate that wildfires can have an impact on the HCN concentrations in the stratosphere for up to 2 years Community Atmosphere Model with Chemistry simulations reproduce increases in CO in October 2015 but underestimate the amount of CO compared to the measurements